Extracting Of Hyaluronic Acid from Different Sources - Ibragimova D.SH; Davletova X.SH; Khayitbayev A.Kh; Sodiqova Mohinur Abdujalil qizi (Genius Journals, 2022)
Hyaluronic acid (HA) is the most common polymer existing in different tissues and liquids of vertebrae animals as well as humans. Hyaluronic acid is known to belong to glycosaminoglycans class. Mucopolysaccharides were isolated from mucus, to which they give viscous lubricating properties. These properties, in turn, are related to glycosaminoglycan’s ability to bind to a significant amount of water. Recently, there has drawn increased attention to extract HA from the tissue of vertebrate animals or from the bacteria that creates the protecting capsule from the polysaccharides. But until now HA extracted mainly from rooster comb. So the main object of this research work is to extract HA from eggshells and bovine tissue; to review obtained substances through the uses of IR analysis
Keywords: Hyaluronic acid; extraction; tissue; bovine